If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3) * x(3x + -6) = 0 Reorder the terms: (3 + 2x) * x(3x + -6) = 0 Reorder the terms: (3 + 2x) * x(-6 + 3x) = 0 Reorder the terms for easier multiplication: x(3 + 2x)(-6 + 3x) = 0 Multiply (3 + 2x) * (-6 + 3x) x(3(-6 + 3x) + 2x * (-6 + 3x)) = 0 x((-6 * 3 + 3x * 3) + 2x * (-6 + 3x)) = 0 x((-18 + 9x) + 2x * (-6 + 3x)) = 0 x(-18 + 9x + (-6 * 2x + 3x * 2x)) = 0 x(-18 + 9x + (-12x + 6x2)) = 0 Combine like terms: 9x + -12x = -3x x(-18 + -3x + 6x2) = 0 (-18 * x + -3x * x + 6x2 * x) = 0 (-18x + -3x2 + 6x3) = 0 Solving -18x + -3x2 + 6x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(-6 + -1x + 2x2) = 0 Factor a trinomial. 3x((-3 + -2x)(2 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3 + -2x)' equal to zero and attempt to solve: Simplifying -3 + -2x = 0 Solving -3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -2x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 0 + 3 -2x = 0 + 3 Combine like terms: 0 + 3 = 3 -2x = 3 Divide each side by '-2'. x = -1.5 Simplifying x = -1.5Subproblem 3
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {0, -1.5, 2}
| 1.5(2a+1)=5(0.5a+0.3)+0.1 | | (0.8g+0.6-0.3)=(0.1-0.2h+0.8g) | | -x-5=3x+19 | | x^2+4*x-7=2*x-4 | | 2x-20=2x+10 | | 5x+(-2)=20 | | (5x-9)(2x+4)= | | -22=-7+3y | | -59+3x=2x+21 | | 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 | | 10000000000000000000000000000+e= | | 12-7x+4x=27 | | x+7.8=3 | | 2(y+3)=a | | 5(-4)+2y=10 | | 3x+9x-83=73 | | 6.5x+3.5y=9.5 | | 5x+75=10x-5 |